Fast microwave-assisted synthesis of Li-stuffed garnets and insights into Li diffusion from muon spin spectroscopy. Issue 5 (13th January 2016) - Amores, Marco; Ashton, Thomas E.; Baker, Peter J.; Cussen, Edmund J.; Corr, Serena A.
Abstract : The synthesis of pure, cubic-phase Al-doped lithium stuffed garnets by fast microwave-assisted methods has been realised and the use of muon spectroscopy to probe and understand in greater detail the Li + diffusion properties demonstrated. Abstract : Lithium-stuffed garnets attract huge attention due to their outstanding potential as solid-state electrolytes for lithium batteries. However, there exists a persistent challenge in the reliable synthesis of these complex functional oxides together with a lack of complete understanding of the lithium-ion diffusion mechanisms in these important materials. Addressing these issues is critical to realizing the application of garnet materials as electrolytes in all solid-state lithium-ion batteries. In this work, a cubic phase garnet of nominal composition Li6.5 Al0.25 La2.92 Zr2 O12 is synthesized through a microwave-assisted solid-state route for the first time, reducing considerably the reaction times and heating temperatures. Lithium-ion diffusion behavior is investigated by electrochemical impedance spectroscopy (EIS) and state-of-art muon spin relaxation (μSR) spectroscopy, displaying activation energies of 0.55 ± 0.03 eV and 0.19 ± 0.01 eV respectively. This difference arises from the high inter-grain resistance, which contributes to the total resistance in EIS measurements. In contrast, μSR acts as a local probe providing insights on the order of the lattice, giving an estimated value of 4.62 × 10 −11 cm 2 s −1 for the lithium diffusion coefficient. These results demonstrate the potential of this lithium-stuffed garnet as a solid-state electrolyte for all-solid state lithium-ion batteries, an area of growing interest in the energy storage community.